When liquid crystalline cellulose flows and relaxes - Teixeira, P. F. (2013)
Cellulose-based liquid crystalline materials can generate stimuli-responsive fibbers and films [1,2]. Changes in orientational order, which can be affected by variation of temperature and UV irradiation as well as by the presence of solvent vapours, give rise to stresses, which result in strains and modifications in sample shape. The processing conditions of the liquid crystalline material are crucial for fibbers and films characteristics. One of the most simple cellulose derivatives that can generate liquid crystalline phases in a wide temperature range is Acetoxypropylcellulose (APC). This behavior enables extrusion in a molten state. Here we characterize, for the first time, the rheological behavior of APC, using slit die rheometry, over a wide range of shear rates, thus extending previous reports where rotational rheometry was employed [3] and thus avoiding possible experimental pitfalls associated with free surface defects. Real-time polarized optical microscopy (Rt-POM) was also applied during measurements. The evolution of APC textures was performed during steady-state and after cessation of shear. The combination of slit die rheometry with Rt-POM has provided crucial information in the understanding of the rich viscoelastic liquid crystalline behavior presented by APC. Both stress relaxation and band texture evolutions are presented and discussed in light of earlier studies carried out at much smaller shear rates [3,4].